On some local restricted Maastrichtian environments of the "Hațeg Island" (Transylvania, Romania) - Codrea, V.; Solomon, Al.; Fărcaș, C.; Barbu, O. (Bulletin of the Geological Society of Greece, 2013)
The continental Maastrichtian formations from Transylvania are notorious mainlyfor bearing peculiar fossils related to an island realm known as the "Hațeg Island". The thick piles of sedimentary rocks accumulated in fluvial environments. The "red beds" are in dominance. However, local peculiar environments are of interest for specific types of fossilization (plants, invertebrates or vertebrates), i.e. ox-bow lakes or fluvial temporary abandoned channels. In such deposits the fossil record can be different compared to the red beds, especially when the oxygen content was low. Case studies as the ones from Pui (Hațeg Basin) or Oarda de Jos (SW Transylvanian Basin) are exposed. The relationships of fossil taxa and these restricted environments are discussed.